The use of protective masks and the level of arterial oxygen saturation at rest and after exercise - Paulina Majek; Angelina Kaleta-Pilarska; Kamil Barański (Nofer Institute of Occupational Medicine, 2022)
Background Studies of influenza, and human coronaviruses provide evidence that the use of a medical mask can prevent the spread of infectious droplets from an infected person to someone else. After global public health emergency of coronavirus SARS-CoV-2 causing illness of COVID-19 was changing frequency of wearing a mask. Therefore, study was undertaken to assess whether the use of protective masks affects the level of oxygen saturation during rest and during exercise. Material and Methods The test consisted of a non-invasive measurement of oxygen saturation by percutaneous determination of arterial oxygen saturation with the use of the pulse oximeter. Oxygen saturation was measured during rest and after physical exertion performed without a protective mask (2 types of masks were used: surgical and FFP2), as well as during rest and after physical exertion performed with the use of a protective mask. The analysis of the oxygen saturation, heart rate, blood pressure and respiratory rate included data on 48 subjects. Results Comparing the post-exercise and pre-exercise values showed a significant difference between all of them. There were no differences found in any variables according to the mask/no-mask status. Conclusions A short-term physical exercise performed in a group of healthy young people using protective masks did not affect oxygen saturation, heart rate, blood pressure and respiratory rate. Med Pr. 2022;73(5):363-68